SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER OBAT MENGGUNAKAN METODE FUZZY TSUKAMOTO - Hamdani .; Deviana Selywita (SISFOTENIKA, 2013)
Abstract : At the pharmacy, supplier selection is crucial. The problems that frequently encountered in the buying process in the Dispensary is the selection process suppliers, a problem commonly found is the problem of the price offered by suppliers, times of delivery and experience of supplier. A decision support system that can perform supplier selection. To do this supplier used a method of determining the Fuzzy Tsukamoto to get a suggestion system or the appropriate supplier selection criteria or conditions that are expected.Theresults obtained with the supplier selection decision support system is the pharmacy to get the sequence results of recommendations supplier selection accordance with the criteria. For the result of calculation from test data a Douperidon drug is PT.Indofarma have 62.236, PT. Dos Ni Roha have 55.9125, and PT.Kalista have 49.9836. Keywords: Pharmacy, Supplier, Fuzzy Tsukamoto, Fuzzy Inference System.